2016
DOI: 10.1016/j.mbs.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Solvability of implicit final size equations for SIR epidemic models

Abstract: Final epidemic size relations play a central role in mathematical epidemiology. These can be written in the form of an implicit equation which is not analytically solvable in most of the cases. While final size relations were derived for several complex models, including multiple infective stages and models in which the durations of stages are arbitrarily distributed, the solvability of those implicit equations have been less studied. In this paper the SIR homogeneous mean-field and pairwise models and the het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The solution is denoted here by b † c , as the b c to be used is slightly different, as it is shown below. The non-principal Lambert Appendix D. Proofs of Equations (102) and (103) With the approximate expression (95), that is useful up to order O(η 2 ), one obtains for corresponding cumulative number fraction, with the substitution ξ = e −bτ /b:…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution is denoted here by b † c , as the b c to be used is slightly different, as it is shown below. The non-principal Lambert Appendix D. Proofs of Equations (102) and (103) With the approximate expression (95), that is useful up to order O(η 2 ), one obtains for corresponding cumulative number fraction, with the substitution ξ = e −bτ /b:…”
Section: Data Availability Statementmentioning
confidence: 99%
“…There are several approaches that investigate the optimal control of the model with time-dependent or nonlinear functions [49,50,55,59,60,62,[67][68][69][70]75,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] and the SIR model had also been applied to networks [34,[94][95][96]. While it is comparably easy to set up a network or agentbased [97][98][99] model or to solve a nonlinear problem numerically, pure analytic works are relatively scarce [100][101][102][103][104][105][106][107][108][109][110][111].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are relatively few articles in which GSPT has been applied rigorously to epidemics models [33,17,14,42,3,39]; however, for most infectious diseases, the presence of different time scales is natural. Moreover, though a SIR model on networks has been studied with moment closure already [1,20], the SIRS extension has not. Likewise, a thorough bifurcation analysis on compartment models such as the one we analyse in this paper is not present in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In Bidari et al. ( 2016 ), Bidari et al studied the solvability of implicit equations for the final epidemic size such as the classical SIR model, the pairwise SIR model and the heterogeneous mean-field SIR model, and proved the convergence of the solution for a suitable fixed point equation. Wang and Cao ( 2021 ) studied the final size of various network SIR models, and showed that how the final epidemic size is related to the basic reproduction number for different degree distributions.…”
Section: Introductionmentioning
confidence: 99%